Art of Beat Style dengan Teknik Cut Out - Dinda Dinda; Fadri Rahmat; Desra Imelda; Mirda Aryadi (INDO PUBLISHING, 2026)
This fashion work is based on the development of fashion that increasingly emphasizes freedom of expression and the exploration of form in design. The Art of beatstyle was chosen as the source of inspiration due to its eccentric, creative, and unconventional visual characteristics. The purpose of this creation is to produce fashion designs that represent freedom of expression through the application of fabric manipulation techniques, particularly the cut-out technique, combined with Sashiko as a decorative element. The creation process consists of several stages, including idea exploration, design development, technical experimentation, pattern making, production, and presentation. Visual inspiration is realized through organic forms applied to the cut-out technique, creating the interplay of space, texture, and visual dimensions within the garments. The Sashiko technique is utilized to enrich surface details and enhance the aesthetic value of the designs. The final collection consists of three fashion categories: Ready-to-Wear entitled “Ruang Celah” (The Space of Gaps), Ready-to-Wear Deluxe entitled “Ruang Tumbuh” (The Growing Space), and Haute Couture entitled “Ruang Antara” (The Space Between). These three works embody the characteristics of Art of beatthrough the use of contrasting colors, organic forms, and increasingly complex cut-out explorations in each category. The collection demonstrates that the cut-out technique functions not only as a decorative element but also as a means of creating an expressive, dynamic, and artistic visual identity in fashion design.